Concept and implementation of integration templating for uPortal environment / Mohd Firdaous Mohd Yousof - Mohd Yousof, Mohd Firdaous (2005)
The usage of portal become popular through the introduction of Yahoo!. Yahoo! provide the ability of each of its user to personalize their account; by uploading and installing pictures in their account. After the success of Yahoo!, there have been many portals being develop and publish in the Internet. Some of the commercial portal published and attracted the most users are portals such as Myspace.com and Friendster.com. Enhancement of the old existing portal so it can be used in universities and academic institutions are being promoted by JA-SiG through the development of uPortal.